A systematic review and meta-analysis on the role of omental or falciform ligament wrapping during pancreaticoduodenectomy. Issue 9 (September 2020) - Andreasi, Valentina; Partelli, Stefano; Crippa, Stefano; Balzano, Gianpaolo; Tamburrino, Domenico; Muffatti, Francesca; Belfiori, Giulio; Cirocchi, Roberto; Falconi, Massimo
Abstract: Background: The role of wrapping in the setting of pancreaticoduodenectomy (PD) is controversial. This study aimed to assess whether the use of omental or falciform ligament wrapping of pancreatic anastomosis and/or vessels could reduce the rate of POPF and postpancreatectomy hemorrhage (PPH) after PD. Methods: Studies comparing PD with (PD-W) and without wrapping (PD-nW) were included. Primary outcomes were POPF and extraluminal PPH. Dichotomous variables were analyzed for risk ratios (RR) with 95% Confidence Intervals. Results: Nine studies involving 4384 patients were considered. The risk of POPF and clinically relevant POPF (CR-POPF) was similar between patients with and without omental wrapping of pancreatic anastomosis when considered as overall. A significant benefit from wrapping in terms of CR-POPF (RR 0.14, P  = 0.002) was reported for patients who underwent PD with pancreaticojejunostomy (PJ). The risk of extraluminal PPH was slightly lower in patients who underwent vessels wrapping compared to those who did not (RR 0.58, P  = 0.020). Similar extraluminal PPH rates were reported for patients with and without wrapping of pancreatic anastomosis ( P  = 0.620). Discussion: Data from low-evidence studies suggest that omental wrapping of PJ may reduce the incidence of CR-POPF, whereas vessels wrapping may have a slight effect for preventing extraluminal PPH.